2021
DOI: 10.1038/s41398-021-01693-0
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Zn2+ potentiates the effects of cocaine on striatal dopamine neurotransmission and behavior

Abstract: Cocaine binds to the dopamine (DA) transporter (DAT) to regulate cocaine reward and seeking behavior. Zinc (Zn2+) also binds to the DAT, but the in vivo relevance of this interaction is unknown. We found that Zn2+ concentrations in postmortem brain (caudate) tissue from humans who died of cocaine overdose were significantly lower than in control subjects. Moreover, the level of striatal Zn2+ content in these subjects negatively correlated with plasma levels of benzoylecgonine, a cocaine metabolite indicative o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Further research found that after ZnT-3 gene knockout, mice became insensitive to increased Zn 2+ in the striatum. The electrically induced release of dopamine (DA) was significantly reduced, the clearance rate of DA was higher [ 124 ], and ARCD was induced, suggesting that there may be ZnT-3-dependent communication between plasma and neuronal zinc through the cerebrovascular wall [ 125 ].…”
Section: Molecular Mechanism Of Zinc-associated Aging and Cognitive I...mentioning
confidence: 99%
See 2 more Smart Citations
“…Further research found that after ZnT-3 gene knockout, mice became insensitive to increased Zn 2+ in the striatum. The electrically induced release of dopamine (DA) was significantly reduced, the clearance rate of DA was higher [ 124 ], and ARCD was induced, suggesting that there may be ZnT-3-dependent communication between plasma and neuronal zinc through the cerebrovascular wall [ 125 ].…”
Section: Molecular Mechanism Of Zinc-associated Aging and Cognitive I...mentioning
confidence: 99%
“…Zinc affects learning and memory and is an important factor in ARCD because it regulates various cellular and molecular processes [ 100 , 248 ]. For example, during brain depolarization [ 101 , 124 ], zinc is released into synapses together with glutamate to regulate synaptic communication and neural plasticity [ 249 ].…”
Section: Interventions For Zinc-associated Aging and Cognitive Impair...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cocaine triggers drug-seeking behavior by binding to the dopamine transporter at the synapse [122,123]. A 2021 study revealed that increased zinc concentrations in mice enhance cocaine binding to the dopamine transporter (DAT) protein.…”
Section: Cocaine Addictionmentioning
confidence: 99%
“…Due to the calcium dependency of cocaine-induced stimulation of DA release, under the same FSCV experimental conditions, changes in free calcium fluctuations were assessed for typical and atypical DAT blockers using fiber photometry procedures. DAT function may be influenced by its interactions with other neuronal membrane proteins, small molecules, and cations [ 22 25 ]. Previous reports have attributed cocaine-induced enhancement of evoked DA release to an increased availability of DA-containing large dense-core vesicles (LDCVs) associated with the synapsin-mediated reserve pool of vesicles under resting conditions [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%